TMOD-21. A NOVEL IN-VITRO METHOD TO MODEL MACROPHAGES IN GLIOBLASTOMA. (12th November 2021) - Alrefai, Hasan; Beierle, Andee; Nassour, Lauren; Eustace, Nicholas; Patel, Zeel; Anderson, Joshua; Hicks, Patricia; King, Peter; Willey, Christopher
Abstract: BACKGROUND: The GBM tumor microenvironment (TME) is comprised of a plethora of cancerous and non-cancerous cells that contribute to GBM growth, invasion, and chemoresistance. In-vitro models of GBM typically fail to incorporate multiple cell types. Others have addressed this problem by employing 3D bioprinting to incorporate astrocytes and macrophages in an extracellular matrix; however, they used serum-containing media and classically polarized anti-inflammatory macrophages. Serum has been shown to cause GBM brain-tumor initiating cells to lose their stem-like properties, highlighting the importance of excluding it from these models. Additionally, tumor-associated macrophages (TAMs) do not adhere to the traditional M2 phenotype. METHODS: THP-1 monocytes and normal human astrocytes (NHAs) were transitioned into serum-free HL-1 and neurobasal-based media, respectively. Monocytes were stimulated towards a macrophage-like state with PMA and polarized by co-culturing them with GBM patient-derived xenograft(PDX) lines, using a transwell insert. CD206 expression was used to validate polarization and a cytokine array was used to characterize the cells. RESULTS: There was no difference in proliferation rates at 72 hours for THP-1 monocytes grown in serum-free HL-1 media compared to serum-containing RPMI 1640 (p > 0.95). Macrophages polarized via transwell inserts expressed the lymphocyte chemoattractant protein, CCL2, whereas resting(M0), pro-inflammatory(M1), and anti-inflammatory(M2) macrophages did not. Additionally, these macrophages expressed more CXCL1 and IL-1ß relative to M1 macrophages. We have also demonstrated a method to maintain a tri-culture model of GBM PDX cells, NHAs, and TAMs in a serum-free media that supports the growth/maintenance of all cell types. CONCLUSIONS: We have demonstrated a novel method by which we can polarize macrophages towards a tumor-supportive phenotype that differs in cytokine expression from traditionally polarized macrophages. This higher-fidelity method of modeling TAMs in GBM can aid in the development of targeted therapeutics that may one day enter the clinic in hopes of improving outcomes in GBM.